(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Taking as a starting point the current state of the Italian legislation and the latest capital judgement of the Constitutional Court in the area of the end of life, the article explores ? from a de iure condendo perspective ? several aspects of the laws and the reality of the health system and of the political culture of Belgium, a country that has highly developed care, services and rights in this area. This is followed by some considerations aiming at identifying possible paths of intervention by the Italian legislator and subsequently possibly prevent a further substitution by the Judiciary.